A In vitro Evaluation of Different Brands of Pantoprazole Tablets Marketed in Sebha City, Libya - Alazraq, Aiyda; Salima Fusary,; Zahra Yagoub, (AlQalam Journal of Medical and Applied Sciences, 2025)
Pantoprazole, a substituted benzimidazole, proton pump inhibitor, is widely used to treat acid-related disorders. This study analyzed five brands of pantoprazole tablets (P1-P5) obtained from local pharmacies in Sebha, Libya, examining each brand’s general appearance, weight uniformity, hardness, friability, and disintegration in both acidic and phosphate buffer medium. The tests were conducted according to procedures outlined in the United States Pharmacopeia. All tablets appeared uniform in color, undamaged, and odorless. The average tablet weights ranged from 103 mg to 204 mg, and all brands met USP standards for weight variation. Hardness testing showed the highest crushing strength in brand P1 (16.6 kg) and the lowest in P4 (7 kg), with all brands meeting USP hardness requirements. Friability testing indicated robust resistance to abrasion, with no significant weight loss observed across brands, suggesting high coating durability. All brands except P4 showed no disintegration in acidic conditions (0.1M HCl). However, in phosphate buffer 0.05M (pH 6.8), the disintegration times ranged from 2 to 20 minutes, meeting the USP criteria for enteric-coated tablets. The study concluded that most pantoprazole t brands available in Sabha met the required quality standards. Brand P4 showed complete disintegration in an acidic medium, indicating potential issues with its enteric coating. Ensuring the consistency and quality of pharmaceutical products is critical for patient safety and treatment effectiveness